Method for predicting thickness of battery and method for designing liquid injection quantity of battery
By fitting the relationship between the free liquid coefficient of the electrolyte and the gap thickness of the free liquid layer, the problem of low accuracy of the traditional battery thickness prediction method is solved, and high-accurate battery thickness prediction is achieved.
Patent Information
- Application Number
- CN202510110444.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
AI Technical Summary
The traditional soft-pack battery thickness prediction method has obvious errors between the design thickness and the actual thickness, resulting in low design accuracy.
By obtaining the relationship curve of the finished battery, the relationship between the coefficient of the electrolyte free liquid and the gap thickness of the free liquid layer is fitted using the formula d=a*EXP(b*P free liquid)+c, and the overall thickness of the battery is calculated.
This method can accurately predict the battery thickness with an error of less than 0.5%, improving the accuracy of battery design and manufacturing.
Smart Images

Figure CN119833907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery design, and in particular to a method for predicting battery thickness and a method for designing battery liquid injection volume. Background Art
[0002] Soft-pack batteries are widely used in electric vehicles, energy storage systems, portable electronic devices and other fields due to their lightweight, high energy density and good safety performance. In the design and production process of soft-pack batteries, accurate prediction of battery thickness is of great significance for optimizing battery design and ensuring effective control of product thickness. Traditional soft-pack battery thickness prediction methods mainly rely on cumulative calculation of the thickness of the pole piece, diaphragm, current collector and aluminum-plastic film. In actual applications, this method has been found to have a significant error between the designed thickness and the actual thickness.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a method for predicting battery thickness and a method for designing battery liquid injection amount. The method for predicting battery thickness takes into account the fluctuation of battery thickness caused by different battery liquid injection amounts and has high accuracy.
[0005] The present invention is achieved in that: In a first aspect, the present invention provides a method for predicting battery thickness, comprising: Get the relationship curve: Disassemble various finished batteries, and various finished batteries are only filled with liquid coefficient P 注液 Different batteries, P 注液 Unit: g / Ah; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery and the amount of liquid absorbed M inside the battery pores; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , unit is g / Ah, where C is the battery capacity, unit is Ah, P 损失 is the loss coefficient of electrolyte during sealing, unit: g / Ah; According to the thickness d of the free liquid layer gap of various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c for fitting, and the constant coefficients a, b, c are obtained by fitting, and the relationship curve is obtained; Battery thickness prediction: When the battery to be predicted has only a liquid filling coefficient P 注液Different from the finished battery, the free liquid layer gap thickness d is calculated through the relationship curve, and the overall thickness of the battery can be calculated based on the free liquid layer gap thickness d.
[0006] In an optional embodiment, the thickness of the free liquid layer gap between the battery electrode and the diaphragm is calculated according to formula A: d=D-(n1*d0-n2*d2-n3*d4-n4*d5) / 1000; Wherein, D is the overall thickness of the battery, in mm; d is the thickness of the free liquid layer gap corresponding to the electrode and the diaphragm of the battery, in mm; n1 is the number of positive electrode sheets or folds in the thickness direction of the battery; d0 is the thickness of a single positive electrode sheet, in μm; d1 is the thickness of the positive current collector, in μm; n2 is the number of negative electrode sheets or folds in the thickness direction of the battery; d2 is the thickness of a single negative electrode sheet, in μm; d3 is the thickness of the negative current collector, in μm; n3 is the number of diaphragm layers or folds in the thickness direction of the battery; d4 is the thickness of a single diaphragm, in μm; n4 is the number of shell layers in the thickness direction of the battery; d5 is the thickness of a single aluminum-plastic film, in μm; In an optional embodiment, when the only difference between the structure and the filling coefficient of the battery to be predicted and the finished battery is the structure and the filling coefficient of the finished battery, according to the formula d'={a*EXP[b*(P 注液 -M' / C'-P 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3') and the formula M'=M / (n1+n2+n3)*(n1'+n2'+n3') are used to calculate the thickness d' of the free liquid layer gap of the battery to be predicted, and then the overall thickness of the battery is calculated according to formula A.
[0007] The structure of the battery to be predicted is different from that of the finished battery in that the number of layers of the separator or the electrode is different. In the formula, n1', n2' and n3' are the number of layers or folds of the positive electrode, the negative electrode and the separator, respectively.
[0008] In an optional embodiment, according to Formula B: M=ρ 电解液 *((S1*(d0-d1) / 10000-S1*(σ 正极片 -σ 正极集流体 )*(W1 / ρ1+W2 / ρ2+……+W n / ρ n ))+(S2*(d2-d3) / 10000-S2*(σ 负极片- σ 负极集流体 )*(W'1 / ρ1'+W2' / ρ2'+……+W n ' / ρ n '))+(h*L*d4-h*L*σ 隔膜 / ρ 隔膜 )) Calculate the amount of liquid absorbed inside the battery pores; Among them, ρ 电解液 is the density of the electrolyte, in g / cm 3 ; S1 is the active layer area of a single positive electrode sheet, in cm 2 ; S2 is the active layer area of a single negative electrode sheet, in cm 2 ; W1, W2...W n is the percentage of the weight of each component of the positive electrode active layer to the weight of the electrode; ρ1, ρ2...ρ n is the true density of each component of the positive electrode active layer, in g / cm 3 ; W1', W2'...W n ' is the percentage of the weight of each component of the negative electrode active layer to the weight of the electrode; ρ1', ρ2'...ρ n ' is the true density of each component of the positive electrode active layer, unit: g / cm 3 ; h is the width of the separator, in cm; L is the length of the separator in a single battery, in cm; ρ 隔膜 is the true density of the diaphragm material, in g / cm 3 .
[0009] In an optional embodiment, when the battery to be predicted has only a liquid filling coefficient P 注液 When the positive electrode area S1'' of the battery to be predicted is different from the finished battery, according to the formula d''={a*EXP[b*(P 注液 -M'' / C''-P 损失 )]+c} / S1*S1' and the formula M''=M / S1*S1' are used to calculate the thickness d'' of the free liquid layer gap, and then the overall thickness of the battery is calculated according to the formula A.
[0010] In an optional embodiment, the filling coefficient of the finished battery is 2.5~5g / Ah.
[0011] In a second aspect, the present invention provides a method for designing a battery liquid injection amount, comprising: Get the relationship curve: Disassemble various finished batteries, and various finished batteries are only filled with liquid coefficient P 注液 Different batteries; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery, in μm, and the amount of liquid absorbed inside the battery pores, in g; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , where C is the battery capacity, unit is Ah, P 损失 is the amount of electrolyte lost during sealing; According to the thickness d of the free liquid layer gap of the various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c is fitted to obtain the relationship curve; Injection volume design: To obtain a battery with a target thickness, the free liquid layer gap thickness d can be calculated based on the target thickness, and the electrolyte injection coefficient P can be further calculated based on the relationship curve. 注液 .
[0012] The present invention has the following beneficial effects: The method for predicting battery thickness or battery injection amount design provided by the embodiment of the present invention, through the preparation method provided by the present invention, by exploring the relationship between the electrolyte free liquid coefficient and the free liquid layer gap thickness, the relationship between the two is obtained, and the corresponding free liquid layer gap thickness under the set electrolyte injection coefficient can be known according to the relationship, and then the overall thickness of the battery can be calculated; or, if a battery of a target thickness is to be obtained, the electrolyte layer gap thickness under the target thickness is calculated, and the layer gap thickness is substituted into the relationship, so that the electrolyte injection coefficient can be determined. The method has high accuracy and can provide guidance for the design and manufacture of batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0014] Figure 1 This is a graph showing the relationship between the gap thickness of the battery layer and the free liquid coefficient in Example 1; Figure 2 This is a graph showing the relationship between the battery layer gap thickness and the free liquid coefficient in Example 2. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0016] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0017] The inventors have considered the problem that the current battery design method leads to a significant error between the design value and the actual value, and found that the main problem is that the existing design method does not take into account the thickness of the interlayer gap between the pole piece and the diaphragm. It is verified that it is this part of the thickness that causes the large error and low accuracy between the actual thickness of the battery and the design thickness. In particular, when the amount of free electrolyte inside the battery changes, the traditional prediction method is more difficult to accurately reflect the change in the interlayer gap thickness, resulting in insufficient accuracy in battery thickness prediction. In view of this, the following solution is proposed: A method for predicting battery thickness provided by an embodiment of the present invention includes: Get the relationship curve: Disassemble a variety of finished batteries, wherein the various finished batteries are only filled with liquid coefficient P 注液 Different batteries; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery, in μm, and the amount of liquid absorbed inside the battery pores, in g; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , where C is the battery capacity, unit is Ah, P 损失 is the amount of electrolyte lost during sealing; According to the thickness d of the free liquid layer gap of the various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 ) to fit and obtain the relationship curve; Battery thickness prediction: When the battery to be predicted has only a liquid filling coefficient P 注液 When the battery is different from the finished product, the free liquid layer gap thickness d is calculated by the relationship curve, and the overall thickness of the battery can be calculated according to the free liquid layer gap thickness d; Alternatively, to obtain a battery with a target thickness, the free liquid layer gap thickness d can be calculated based on the target thickness, and the electrolyte injection coefficient P can be further calculated based on the relationship curve. 注液 .
[0018] The preparation method provided by the present invention obtains a relational formula by exploring the relationship between the electrolyte free liquid coefficient and the free liquid layer gap thickness. According to the relational formula, the corresponding free liquid layer gap thickness under the set electrolyte injection coefficient can be known, and then the overall thickness of the battery can be calculated. The method has high accuracy and can provide guidance for the design and manufacture of batteries.
[0019] The specific prediction method is: S1. Prepare materials Take the positive / negative current collector, positive / negative electrode sheet and separator, test the current collector, electrode sheet and separator area, according to the formula σ=W / S, σ is the surface density, unit is g / cm 2 ; W is the mass of the sample, in g; S is the effective area of the sample, in cm 2 , the positive electrode current collector surface density σ is calculated 正极集流体 , σ 正极片 , σ 负极集流体 , σ 负极片 and σ 隔膜 .
[0020] S2. Preparation of finished battery The positive and negative electrodes and separators are assembled into multiple dry cells with the same structure, and electrolytes with gradient weights (i.e. gradient injection coefficients) are injected in sequence. After sealing, the cells are formed and divided into different capacities to form finished batteries. The electrolyte injection volume ranges from 2.5 to 5 g / Ah.
[0021] S3. Measure the thickness of the free liquid layer gap and the amount of liquid absorbed The finished batteries with different electrolyte injection amounts were disassembled, the thickness of each component inside the battery was tested, and the thickness of the free liquid layer gap in the battery was calculated according to formula A: d=D-(n1*d0-n2*d2-n3*d4-n4*d5) / 1000 calculates the corresponding free liquid layer gap thickness d between the battery pole piece and the diaphragm, unit: mm; Wherein, D is the overall thickness of the battery, in mm; n1 is the number of positive electrode sheet layers or folds in the thickness direction of the battery; d0 is the thickness of a single positive electrode sheet, in μm; d1 is the thickness of the positive electrode collector, in μm; n2 is the number of negative electrode sheet layers or folds in the thickness direction of the battery; d2 is the thickness of a single negative electrode sheet, in μm; d3 is the thickness of the negative electrode collector, in μm; n3 is the number of diaphragm layers or folds in the thickness direction of the battery; d4 is the thickness of a single diaphragm, in μm; n4 is the number of shell layers in the thickness direction of the battery; d5 is the thickness of a single aluminum-plastic film, in μm.
[0022] The amount of liquid absorbed by the battery internal pole piece is calculated according to Formula B, where the amount of liquid absorbed by the internal pores of the battery is recorded as M, in g. Formula B: M=ρ 电解液 *((S1*(d0-d1) / 10000-S1*(σ 正极片 -σ 正极集流体 )*(W1 / ρ1+W2 / ρ2+……+W n / ρ n ))+(S2*(d2-d3) / 10000-S2*(σ 负极片- σ 负极集流体 )*(W'1 / ρ1'+W2' / ρ2'+……+Wn ' / ρ n '))+(h*L*d4-h*L*σ 隔膜 / ρ 隔膜 )) Calculate the amount of liquid absorbed inside the battery pores; Among them, ρ 电解液 is the density of the electrolyte, in g / cm 3 ; S1 is the active layer area of a single positive electrode sheet, in cm 2 ; S2 is the active layer area of a single negative electrode sheet, in cm 2 ; W1, W2...W n is the percentage of the weight of each component of the positive electrode active layer to the weight of the electrode; ρ1, ρ2...ρ n is the true density of each component of the positive electrode active layer, in g / cm 3 ; W1', W2'...W n ' is the percentage of the weight of each component of the negative electrode active layer to the weight of the electrode; ρ1', ρ2'...ρ n ' is the true density of each component of the positive electrode active layer, unit: g / cm 3 ; h is the width of the separator, in cm; L is the length of the separator in a single battery, in cm; ρ 隔膜 is the true density of the diaphragm material, in g / cm 3 .
[0023] S5. Curve fitting According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P of each battery 游离液 , where C is the battery capacity, unit is Ah, P 损失 is the amount of electrolyte lost during sealing. If there is loss during battery sealing, then P 损失 Not zero, if there is no loss then P 损失 is zero.
[0024] According to the calculated free liquid layer gap thickness d and electrolyte free liquid coefficient P of various batteries 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c are fitted to obtain the relationship curve.
[0025] S6. Thickness prediction When the battery to be predicted has only a liquid filling coefficient P 注液 Different from the finished battery, the free liquid layer gap thickness d is calculated by the relationship curve, and the overall thickness of the battery can be calculated based on the free liquid layer gap thickness d.
[0026] Optionally, when the only difference between the structure and the filling coefficient of the battery to be predicted and the finished battery is the finished battery, according to the formula d'={a*EXP[b*(P 注液 -M' / C'-P 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3') and the formula M'=M / (n1+n2+n3)*(n1'+n2'+n3') to calculate the free liquid layer gap thickness d'' of the battery to be predicted, and then calculate the overall thickness of the battery according to the formula A; the structure of the battery to be predicted is different from that of the finished battery in that the number of layers of the diaphragm or the electrode is different, wherein n1', n2' and n3' are the number of layers or folds of the positive electrode, the negative electrode and the diaphragm respectively.
[0027] Calculation based on the above two formulas is a fast calculation method with high efficiency.
[0028] When the battery structure changes (the number of pole pieces and diaphragm layers changes), the thickness of the free liquid layer gap d' after the change is related to the d of the battery before the change: d'=d / (n1+n2+n3)*(n1'+n2'+n3'); combined with the formula d=a*EXP(b*P 游离液 ) + c and the formula P 游离液 =P 注液 -M / CP 损失 The formula d'={a*EXP[b*(P 注液 -M' / C'-P 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3').
[0029] Optionally, when the battery to be predicted has only a filling coefficient P 注液 When the positive electrode area S1'' of the battery to be predicted is different from the finished battery, according to the formula d''={a*EXP[b*(P 注液 -M'' / C''-P 损失 )]+c} / S1*S1' and the formula M''=M / S1*S1' are used to calculate the thickness d'' of the free liquid layer gap, and then the overall thickness of the battery is calculated according to the formula A.
[0030] When the area of the positive electrode sheet changes, the thickness of the free liquid layer gap d'' of the battery after the change is related to the d of the battery before the change: d''=d / S1*S1'; combined with the formula d=a*EXP(b*P 游离液 ) + c and the formula P 游离液 =P 注液 -M / CP 损失 The formula d''={a*EXP[b*(P 注液 -M'' / C''-P 损失)]+c} / S1*S1'.
[0031] When the battery's pole piece (active layer formula, active layer material, density and thickness), separator (material, thickness), electrolyte (formula, density), current collector (material, density, thickness, etc.) parameters involved in the calculation in S5 are significantly adjusted, steps S1 to S5 need to be repeated to re-predict the relationship curve in step 6.
[0032] The embodiment of the present invention also provides a method for designing the amount of liquid injected into a battery, which includes: Get the relationship curve: Disassemble a variety of finished batteries, wherein the various finished batteries are only filled with liquid coefficient P 注液 Different batteries; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery, in μm, and the amount of liquid absorbed inside the battery pores, in g; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , where C is the battery capacity, unit is Ah, P 损失 is the amount of electrolyte lost during sealing; According to the thickness d of the free liquid layer gap of the various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c is fitted to obtain the relationship curve; Injection volume design: To obtain a battery with a target thickness, the free liquid layer gap thickness d can be calculated based on the target thickness, and the electrolyte injection coefficient P can be further calculated based on the relationship curve. 注液 .
[0033] Specifically, this method is the same as steps S1 to S5 of the aforementioned method for predicting battery thickness. The only difference is that the free liquid layer gap thickness d and the corresponding electrolyte free liquid coefficient P obtained by steps S1 to S5 are used. 游离液 The relationship between is used to design the injection volume suitable for the target thickness battery.
[0034] Example 1 (1) Obtaining the relationship curve Preparation of positive electrode sheet: The positive electrode slurry is coated on the surface of aluminum foil. The solid material of the positive electrode slurry is composed of lithium iron phosphate, binder (PVDF) and conductive agent (SP) in a mass ratio of 96:2:2; the thickness of the aluminum foil is 13μm and the surface density is 3.5mg / cm 2The surface density of the active layer formed by the positive electrode slurry is 27.54 mg / cm 2 The active layer area on each side of the positive electrode is 485.1 cm 2 .
[0035] Preparation of negative electrode sheet: The negative electrode slurry is coated on the surface of aluminum foil. The solid material of the negative electrode slurry is composed of graphite, SBR, CMC and conductive agent (SP) with a mass ratio of 94:2:2:2; the thickness of the copper foil is 6μm and the surface density is 5.3mg / cm 2 The surface density of the active layer formed by the negative electrode slurry is 14.77 mg / cm 2 The area of the active layer on each side of the negative electrode is 502.3 cm 2 .
[0036] The density of the positive electrode lithium iron phosphate is 3.60g / cm 3 The density of the positive electrode conductive agent is 2.20 g / cm 3 The density of the positive electrode binder is 1.78 g / cm 3 The true density of negative electrode graphite is 2.23g / cm 3 The density of negative electrode CMC is 0.60g / cm 3 The density of negative electrode SBR is 1.02g / cm 3 The density of the negative electrode conductive agent is 2.20 g / cm 3 , the density of the electrolyte is 1.210 g / cm 3 , the density of PP is 0.905g / cm 3 , Diaphragm: PP material, thickness 25μm, width 342mm, surface density 1.2mg / cm 2 .
[0037] 54 positive electrode sheets and 55 negative electrode sheets were stacked in a Z-shape with a separator of 1644.5 cm in length, covered with an aluminum-plastic film, and assembled into multiple dry cells with the same structure. Electrolytes of multiple gradient weight values were injected respectively as shown in Table 1. After injection, the cells were sealed and weighed to confirm that the weight loss of the electrolyte was 0.00 g. After formation and capacity division, a finished battery with a capacity of 100 Ah was obtained.
[0038] Each finished battery was disassembled and the thickness D of the finished battery and the thickness of each internal component were tested. The average thickness of the positive electrode sheet after capacity separation was 144.2μm, and the average thickness of the negative electrode sheet after capacity separation was 132.1μm.
[0039] According to formula A, the thickness d of the gap between the free liquid layer in the battery is calculated. According to formula B, the liquid absorption M of the internal electrode of the battery is calculated to be 428.1g (since only the injection amount is different, M is the same). 游离液 =P注液 -M / CP 损失 , P 损失 is 0, and P is calculated 游离液 .
[0040] Table 1 Statistics of different battery thicknesses and layer gaps corresponding to different injection volumes
[0041] According to the measured multiple d and the corresponding P 游离液 According to the formula d=a*EXP(b*P 游离液 )+c for fitting, such as Figure 1 As shown, the relationship curve d=0.1075*EXP(2.6857*P 游离液 )+0.0793.
[0042] (2) Verify the validity of the relationship curve Take 5 dry cells that are the same as the finished battery in (1) and use the P in Table 2 注液 The electrolyte was injected and sealed without electrolyte loss. After formation and capacity separation, the experimental battery was obtained. Since the dry battery used in this step is the same as that in (1), M / C is consistent with the calculation result of step (1), so P 游离液 See Table 2, through the formula d = 0.10641 * P 游离液 *EXP(2.7686* P 游离液 )+0.07011. Obtain the thickness d of the free liquid layer gap corresponding to each positive electrode layer of the battery 预测 , the battery thickness D is predicted by calculation.
[0043] The five experimental batteries were disassembled, and the thickness of each diaphragm, positive and negative electrode sheets, as well as the thickness of the outer shell were measured. The average free liquid layer gap thickness d corresponding to each positive electrode sheet of the actual battery of the five experimental batteries was calculated. 实际 And the actual battery thickness D 实际 . Record the test results in Table 2.
[0044] Table 2 Experimental group test data records
[0045] The error between the predicted battery thickness and the actual battery thickness is less than 0.5%, which is extremely small. This shows that the method for predicting the battery thickness provided by the present invention has better reliability.
[0046] Example 2 (1) Obtaining the relationship curve Preparation of positive electrode sheet: The positive electrode slurry is coated on the surface of aluminum foil. The solid material of the positive electrode slurry is composed of lithium iron phosphate, binder (PVDF) and conductive agent (SP) in a mass ratio of 96:2:2; the thickness of the aluminum foil is 13μm and the surface density is 3.5mg / cm 2 The surface density of the active layer formed by the positive electrode slurry is 35.40 mg / cm 2 The active layer area on each side of the positive electrode is 308.7 cm 2 .
[0047] Preparation of negative electrode sheet: The negative electrode slurry is coated on the surface of aluminum foil. The solid material of the negative electrode slurry is composed of graphite, SBR, CMC and conductive agent (SP) with a mass ratio of 94:2:2:2; the thickness of the copper foil is 6μm and the surface density is 5.3mg / cm 2 The surface density of the active layer formed by the negative electrode slurry is 17.40 mg / cm 2 The area of the active layer on each side of the negative electrode is 322.9 cm 2 .
[0048] The density of the positive electrode lithium iron phosphate is 3.60g / cm 3 The density of the positive electrode conductive agent is 2.20 g / cm 3 The density of the positive electrode binder is 1.78 g / cm 3 The true density of negative electrode graphite is 2.23g / cm 3 The density of negative electrode CMC is 0.60g / cm 3 The density of negative electrode SBR is 1.02g / cm 3 The density of the negative electrode conductive agent is 2.20 g / cm 3 , the density of the electrolyte is 1.210 g / cm 3 , the density of PP is 0.905g / cm 3 .
[0049] Diaphragm: PP material, thickness 14μm, width 222mm, surface density 0.8mg / cm 2 .
[0050] 33 positive plates and 34 negative plates were stacked in a Z-shaped pattern with a separator of 1016.6 cm in length, covered with aluminum-plastic film, and assembled into multiple dry cells with the same structure. Electrolytes with multiple gradient weight values were injected respectively as shown in Table 3. After injection, the cells were sealed and weighed to confirm the weight loss of the electrolyte. P was calculated. 损失 After formation and capacity division, a finished battery with a capacity of 50Ah is obtained.
[0051] Each finished battery was disassembled and the thickness D of the finished battery and the thickness of each internal component were tested. The average thickness of the positive electrode sheet after capacity separation was 164.3μm, and the average thickness of the negative electrode sheet after capacity separation was 134.8μm.
[0052] According to formula A, the thickness d of the gap between the free liquid layer in the battery is calculated. According to formula B, the liquid absorption M of the internal electrode of the battery is calculated to be 134.65g (because only the injection amount is different, M is the same). 游离液 =P 注液 -M / CP 损失 , P 损失 is 0g / Ah, and P is calculated 游离液 .
[0053] Table 3 Statistics of different battery thickness and layer gap corresponding to different injection volumes
[0054] According to the measured multiple d and the corresponding P 游离液 According to the formula d=a*EXP(b*P 游离液 )+c for fitting, such as Figure 2 As shown, the relationship curve d=0.0203*EXP(4.7150*P 游离液 )+0.1075.
[0055] (2) Verify the validity of the relationship curve Take 5 dry cells that are the same as the finished battery in (1) and use the P in Table 4 注液 The electrolyte was injected and sealed without electrolyte loss. After formation and capacity separation, the experimental battery was obtained. Since the dry battery used in this step is the same as that in (1), M / C is consistent with the calculation result of step (1), so P 游离液 See Table 4, through the formula d = 0.0203 * EXP (4.7150 * P 游离液 )+0.1075. Obtain the thickness d of the free liquid layer gap corresponding to each positive electrode layer of the battery 预测 , the battery thickness D is predicted by calculation.
[0056] The five experimental batteries were disassembled, and the thickness of each diaphragm, positive and negative electrode sheets, as well as the thickness of the outer shell were measured. The average free liquid layer gap thickness d corresponding to each positive electrode sheet of the actual battery of the five experimental batteries was calculated. 实际 And the actual battery thickness D 实际 . Record the test results in Table 4.
[0057] Table 4 Experimental group test data records
[0058] The error between the predicted battery thickness and the actual battery thickness is less than 0.5%, which is extremely small. This shows that the method for predicting the battery thickness provided by the present invention has better reliability.
[0059] Example 3 The finished battery structure used in this embodiment is basically the same as that in embodiment 1, except that the number of layers of the electrode sheet and the separator is different. This battery is named experimental battery A. In this embodiment, the number of layers of the positive electrode sheet, negative electrode sheet and separator of experimental battery A is 27, 28 and 56 respectively.
[0060] The injection is performed with different injection coefficients in Table 5, and the formula d'={a*EXP[b*(P 注液 -M / CP 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3')=0.05651*P 游离液 *EXP(2.7686*P 游离液 )+0.03724 to obtain different free liquid layer gaps, and further calculate the overall thickness of the battery, which is recorded in Table 5.
[0061] Table 5 Statistics of different battery thickness and layer gap corresponding to different injection volumes
[0062] Verify the validity of the above settlement results: Take 5 dry cells identical to those in the experimental battery A and use the P 注液 The electrolyte was injected and sealed without loss of electrolyte. Experimental battery B was obtained after formation and capacity separation.
[0063] The error between the predicted battery thickness and the actual battery thickness is less than 1%, which is extremely small, indicating that the method for predicting the battery thickness provided by the present invention has better reliability.
[0064] Example 4 The finished battery structure used in this embodiment is basically the same as that used in embodiment 2, except that the number of layers of the electrode sheet and the separator is different. The battery is named experimental battery A. In this embodiment, the number of layers of the positive electrode sheet, negative electrode sheet and separator of experimental battery A is 24, 25 and 50 respectively.
[0065] The injection is performed with different injection coefficients in Table 5, and the formula d'={a*EXP[b*(P 注液 -M / CP 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3')=0.01489*P 游离液 *EXP(4.7150*P 游离液)+0.07883 to obtain different free liquid layer gaps, and further calculate the overall thickness of the battery, which is recorded in Table 6.
[0066] Table 6 Statistics of different battery thicknesses and layer gaps corresponding to different injection volumes
[0067] Verify the validity of the above settlement results: Take 5 dry cells identical to the experimental battery A, inject them with the P injection solution in Table 6 respectively, seal them without electrolyte loss, and obtain the experimental battery B after formation and capacity division.
[0068] The error between the predicted battery thickness and the actual battery thickness is less than 1%, which is extremely small, indicating that the method for predicting the battery thickness provided by the present invention has better reliability.
[0069] In summary, the method for predicting battery thickness or battery injection amount design provided by the embodiment of the present invention, through the preparation method provided by the present invention, by exploring the relationship between the electrolyte free liquid coefficient and the free liquid layer gap thickness, the relationship between the two is obtained, and the corresponding free liquid layer gap thickness under the set electrolyte injection coefficient can be known according to the relationship, and then the overall thickness of the battery can be calculated; or, if a battery of a target thickness is to be obtained, the electrolyte layer gap thickness under the target thickness is calculated, and the layer gap thickness is brought into the relationship, so that the electrolyte injection coefficient can be determined. This method has high accuracy and can provide guidance for the design and manufacture of batteries.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for predicting battery thickness, characterized in that: include: Get the relationship curve: Disassemble a variety of finished batteries, wherein the various finished batteries are only filled with liquid coefficient P 注液 Different batteries, P 注液 Unit: g / Ah; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery and the amount of liquid absorbed M inside the battery pores; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , unit is g / Ah, where C is the battery capacity, unit is Ah, P 损失 is the loss coefficient of electrolyte during sealing, unit: g / Ah; According to the thickness d of the free liquid layer gap of the various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c for fitting, and the constant coefficients a, b, c are obtained by fitting, and the relationship curve is obtained; Battery thickness prediction: When the battery to be predicted has only a liquid filling coefficient P 注液 Different from the finished battery, the free liquid layer gap thickness d is calculated by the relationship curve, and the overall thickness of the battery can be calculated based on the free liquid layer gap thickness d.
2. The method according to claim 1, characterized in that According to formula A: d=D-(n1*d0-n2*d2-n3*d4-n4*d5) / 1000, the thickness of the free liquid layer gap between the battery electrode and the diaphragm is calculated; Wherein, D is the overall thickness of the battery, in mm; d is the thickness of the free liquid layer gap corresponding to the electrode and the diaphragm of the battery, in mm; n1 is the number of positive electrode layers or folds in the thickness direction of the battery; d0 is the thickness of a single positive electrode sheet, in μm; d1 is the thickness of the positive current collector, in μm; n2 is the number of negative electrode layers or folds in the thickness direction of the battery; d2 is the thickness of a single negative electrode sheet, in μm; d3 is the thickness of the negative current collector, in μm; n3 is the number of diaphragm layers or folds in the thickness direction of the battery; d4 is the thickness of a single-layer diaphragm, in μm; n4 is the number of shell layers in the thickness direction of the battery; d5 is the thickness of a single-layer aluminum-plastic film, in μm.
3. The method according to claim 2, characterized in that When the predicted battery is different from the finished battery in terms of structure and filling coefficient, according to the formula d'={a*EXP[b*(P 注液 -M' / C'-P 损失 )]+c} / (n1+n2+n3)*(n1'+n2'+n3') and the formula M'=M / (n1+n2+n3)*(n1'+n2'+n3') to calculate the free liquid layer gap thickness d' of the battery to be predicted, and then calculate the overall thickness of the battery according to the formula A. The structure of the battery to be predicted is different from that of the finished battery in that the number of layers of the separator or the electrode is different. In the formula, n1', n2' and n3' are the number of layers or folds of the positive electrode, the negative electrode and the separator, respectively.
4. The method according to claim 2, characterized in that: According to formula B: M=ρ 电解液 *((S1*(d0-d1) / 10000-S1*(σ 正极片 -σ 正极集流体 )*(W1 / ρ1+W2 / ρ2+……+W n / ρ n ))+(S2*(d2-d3) / 10000-S2*(σ 负极片- σ 负极集流体 )*(W'1 / ρ1'+W2' / ρ2'+……+W n ' / ρ n '))+(h*L*d4-h*L*σ 隔膜 / ρ 隔膜 )) Calculate the amount of liquid absorbed inside the battery pores; Among them, ρ 电解液 is the density of the electrolyte, in g / cm 3 ; S1 is the active layer area of a single positive electrode sheet, in cm 2 ; S2 is the active layer area of a single negative electrode sheet, in cm 2 ; W1, W2...W n is the percentage of the weight of each component of the positive electrode active layer to the weight of the electrode; ρ1, ρ2...ρ n is the true density of each component of the positive electrode active layer, in g / cm 3 ; W1', W2'...W n ' is the percentage of the weight of each component of the negative electrode active layer to the weight of the electrode; ρ1', ρ2'...ρ n ' is the true density of each component of the positive electrode active layer, unit: g / cm 3 ; h is the width of the separator, in cm; L is the length of the separator in a single battery, in cm; ρ 隔膜 is the true density of the diaphragm material, in g / cm 3 .
5. The method according to claim 1, characterized in that When the battery to be predicted has only a liquid filling coefficient P 注液 When the positive electrode area S1'' of the battery to be predicted is different from the finished battery, according to the formula d''={a*EXP[b*(P 注液 -M'' / C''-P 损失 )]+c} / S1*S1' and the formula M''=M / S1*S1' are used to calculate the thickness d'' of the free liquid layer gap, and then the overall thickness of the battery is calculated according to the formula A.
6. The method according to claim 1, characterized in that The injection coefficient of the finished battery is 2.5~5g / Ah.
7. A method for designing battery liquid filling volume, characterized in that: include: Get the relationship curve: Disassemble a variety of finished batteries, wherein the various finished batteries are only filled with liquid coefficient P 注液 Different batteries; Test the thickness d of the free liquid layer gap corresponding to each positive electrode sheet of the disassembled battery, in μm, and the amount of liquid absorbed inside the battery pores, in g; According to the formula P 游离液 =P 注液 -M / CP 损失 , calculate the electrolyte free liquid coefficient P 游离液 , where C is the battery capacity, unit is Ah, P 损失 is the amount of electrolyte lost during sealing; According to the thickness d of the free liquid layer gap of the various finished batteries and the corresponding electrolyte free liquid coefficient P 游离液 Data, according to the formula d=a*EXP(b*P 游离液 )+c is fitted to obtain the relationship curve; Injection volume design: To obtain a battery with a target thickness, the free liquid layer gap thickness d can be calculated based on the target thickness, and the electrolyte injection coefficient P can be further calculated based on the relationship curve. 注液 .